Predicting HDR Competency in Human Embryos via Transcriptomic Profiling of DNA Repair Pathways - Serena, Deborah (Journal of Neonatal Surgery, 2025)
Genome editing in early human embryos holds transformative potential but remains limited by the cell’s natural tendency to repair DNA breaks using error-prone pathways like non-homologous end joining (NHEJ). In contrast, homology-directed repair (HDR)—required for precise genome editing—is less efficient and poorly characterized in embryonic contexts. In this study, a computational analysis of publicly available single-cell RNA-sequencing data (GSE66507) from 30 human blastocyst cells to profile the transcriptional activity of DNA repair genes is performed. The key players in NHEJ (e.g., XRCC6, XRCC4) and HDR (e.g., RAD51, BRCA1) across three embryonic lineages: trophectoderm (TE), epiblast (EPI), and primitive endoderm (PE) are examined. The results show that NHEJ-related genes are consistently expressed across all cells, suggesting a default repair mechanism during preimplantation development. HDR genes, on the other hand, show greater variability and are selectively enriched in EPI cells—pointing to a potential transcriptional window of increased HDR activity following embryonic genome activation (EGA). Principal component analysis (PCA) further confirms lineage-specific clustering driven by repair gene expression. These findings highlight how transcriptional profiling can offer valuable clues about repair pathway preferences in early embryos—and guide genome editing strategies toward higher precision and efficiency